Ward Management Basics for the Senior Medical Student Entering Surgery: Part B - Mara B. Antonoff; Jonathan D'Cunha (Association of American Medical Colleges, 2012)
Abstract Introduction Significant recent attention has been directed toward developing preparatory courses to heighten the readiness of senior medical students as they transition to surgical residency. To this end, this resource includes comprehensive materials intended to prepare senior medical students for basic ward management of surgical inpatients. This resource may be used by course directors for surgery PGY-1 preparatory classes/bootcamps, for independent study by individuals planning to matriculate into surgical residencies, or as a review source for those already in surgical training. While these materials were designed to meet the needs of new surgical house staff, the contents are easily generalizable to other medical specialties, and would prove useful for any trainee managing hospital inpatients. Please note that this resource was divided into Parts A and B for MedEdPORTAL organizational purposes; however, all modules in Parts A and B are complementary and together create the complete package of Ward Management Basics for the Senior Medical Student Entering Surgery resource. Methods The materials provided in this module are designed for use as part of a preparatory course for fourth-year medical students entering surgical specialties; all necessary materials including instructor's blueprints, powerpoint slides, and handouts are included. The resource is comprised of eight separate sections on the topics of: patient tracking, documentation, discharge, radiology, antibiotics, signouts, cross coverage, and ward management. A multiple-choice knowledge pre-/posttesttest is also included. The outcomes from this course have been extensively studied. Through pre- and postcourse surveys, knowledge tests, and technical examinations, we measured confidence and skill acquisition in specific job-related tasks. We subsequently followed course participants and matched peers into internship and collected performance evaluations from supervising senior residents, in order to determine if course graduates would display performance advantages in these same instructed tasks. Results In 2010, 62 individuals were studied (22 course graduates, 16 PGY-1 nonparticipant controls at our home institution, and 24 nonparticipant peer controls at outside institutions). We found that course participants demonstrated marked improvement in task-specific confidence in all tasks from course beginning to end, and this was supported by improved scores on written and technical skill examinations. Further, course participants outperformed peers in all tasks 1 month into internship, with their performance advantage predictably dissipating into the third month of residency. Discussion We found that competency-based preparation for surgical internship utilizing the curricular tools found within this resource resulted in objective gains in task-specific confidence and test performance at course conclusion, which, importantly, translated to improved performance upon residency matriculation. These data emphasize the significant impact of these curricular materials in formally preparing senior medical students for the care of surgical inpatient.